Chapter 3.3 Understanding Organisational Structures in RMA – An Overview of Structures and Cases in a Global Context - Fernanda Stringassi de Oliveira; Alice Trentini; Susi Poli (Emerald Publishing Limited, 2023)
The aim of this chapter is to describe a four-type model of organisational structures and to discuss two cases, Embrapa and the Brazilian Agricultural Research Corporation, as well as additional cases at SAM-Research and the centre for shared medical support services established at the University of Bologna. These cases should help readers understand the importance of designing distinctive, tailored-made support services while keeping these structures flexible for further adaptation under unforeseen changes. The chapter concludes by stressing the role of institutions to steadily invest in the design of these tailored support structures and in personalised training for their support staff.
10.1108/978-1-80382-701-820231021; 10.1108/978-1-80382-701-820231021; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262